PENANGGULANGAN TINDAK PIDANA PERKOSAAN TERHADAP ANAK DI BAWAH UMUR ( STUDI KASUS DI POLRES TABANAN ) - Beda Awa, Bambang Anom Partha; Tjatrayasa, I Made; Yusa Darmadi, A.A. Ngurah (Kertha Negara : Journal Ilmu Hukum; Vol. 01, no. 01, Maret 2013, 2013)
Regarding the issue of the children, they often get the wrong treatment, especially the problem of sexual crimes. Children are often victims of sexual crimes in particular rape committed by adults and who are victims are minors. Therefore, this paper will describe the efforts of crime prevention rape of minors and contributing factor in the regional police of Tabanan . Based on the research directly in Tabanan district police, high children’s rape case that occurred in the region of Tabanan is police in because of many factors whicht cause crime of rape, these the were factors less parental supervision, alcohol factor and up to a factor vcd porn adult dating , so that the many factors rape of children especially in Tabanan is police then there must also be tackled in order to create safety in the community, especially in children. countermeasures be undertaken by the police was to provide socialization Tabanan’s police to schools, eradicating alcohol and porn vcd to improve security in the district police of tabanan.
Keywords: Countermeasures, Rape, Child